Mechanical and microstructural properties of GGBFS–RHA geopolymer concrete. Issue 4 (23rd October 2018) - Zabihi, Seyed Mahmoud; Tavakoli, Hamid Reza
Abstract : The current study aims to evaluate the suitability of ground granulated blast-furnace slag (GGBFS)- and rice husk ash (RHA)-based geopolymer concrete for construction of structural elements by using high amounts of the industrial and agricultural solid wastes as raw materials. Compressive and splitting tensile strength, shrinkage and rapid chloride permeability tests were carried out to investigate the geopolymer's properties. The test results indicated that replacement of cement with GGBFS–RHA-based geopolymer improved the mechanical properties of concrete and 100% replacement with the geopolymer can be considered as having the best results from environmental, structural and economic points of view. Furthermore, the curing time affected the compressive strength significantly. In addition, the carbon dioxide (CO2 ) emmision will be significant with the construction of studied sustainable GGBFS–RHA-based geopolymer composites. Moreover, from a microstructural point of view, total incorporation of GGBFS–RHA-based geopolymer in composites led to pore refinement in both the matrix and the interfacial zones and a reduction in the width of the interfacial transition zone between the paste and the aggregate, which could efficiently reduce water permeability.